Uptake, depuration and sublethal effects of the neonicotinoid, imidacloprid, exposure in Sydney rock oysters. (September 2019) - Ewere, Endurance E.; Powell, Daniel; Rudd, David; Reichelt-Brushett, Amanda; Mouatt, Peter; Voelcker, Nicolas H.; Benkendorff, Kirsten
Abstract: The broad utilisation of imidacloprid (IMI) in agriculture poses an increasing risk to aquatic organisms. However, the potential impacts on commercially important shellfish and chemical residues after exposure, are yet to be assessed. We investigated the levels of IMI in Sydney rock oyster (SRO) tissue during a three-day uptake and four-day depuration cycle using liquid chromatography-mass spectrometry. IMI was absorbed from the water, with significantly higher concentrations in the adductor muscles than the gills and digestive glands. Depuration was also fast with a significant drop in tissue concentrations after one day in clean water and complete elimination from all tissues except the digestive gland after four days. The distribution of IMI in SRO after direct exposure using mass spectrometry imaging demonstrated uptake and spatially resolved metabolism to hydroxyl-IMI in the digestive gland and IMI-olefin in the gills. We assessed the effects of IMI on filtration rate (FR), acetylcholinesterase (AChE) activity in the gills, and gene expression profiles in the digestive gland using transcriptomics. Exposure to 2 mg/L IMI reduced the FR of oysters on the first day, while exposure to 0.5 and 1 mg/L reduced FR on day four. IMI reduced the gill AChE activity and altered the digestive gland gene expression profile. This study indicates that commercially farmed SRO can uptake IMI from the water, but negative impacts were only detected at concentrations higher than currently detected in estuarine environments and the chemical residues can be effectively eliminated using simple depuration in clean water. Highlights: Imidacloprid (IMI) was detected in oyster tissues by LC-MS after 1 day exposure in water. Mass spectrometry imaging revealed the distribution of IMI and metabolites in the oyster tissues. Feeding rate and the gill acetylcholinesterase activity were only affected by IMI above environmental concentrations. The gene expression profile in the digestive gland was altered by exposure to a high concentration of IMI exposure. Simple depuration in clean water eliminated IMI from oyster tissues.